Effects of acute static stretching of the throwing shoulder on pitching performance of National Collegiate Athletic Association Division III baseball players - Haag, S. J.; Wright, G. A.; Gillette, C. M.; Greany, J. F. (The Journal of Strength and Conditioning Research, 2010)
Stretching is a common component of an athletic warm-up even though many studies have demonstrated that pre-event static stretching can decrease strength and power performance. The purpose of this study was to examine the effects of acute static stretching of the throwing shoulder on pitching velocity and accuracy of National Collegiate Athletic Association Division III baseball players. Twelve collegiate baseball players, including 6 pitchers and 6 position players, participated in the study. Each participant completed 2 separate testing protocols over a span of 4-6 days. In the experimental condition (SS), 6 static stretches were applied to the throwing shoulder after an active warm-up. After a rest period of 5-10 minutes, participants were allowed 5 warm-up pitches from a pitching mound. Participants then threw 10 pitches measured for velocity and accuracy. The control condition (NS) followed the same procedure but did not include the 6 static stretches. Testing was conducted in an indoor practice facility during normal team practice. No significant differences were found in average velocity, maximum velocity, or accuracy measures when comparing the SS and NS conditions. These results suggest that acute static stretching of the throwing shoulder does not have a significant impact on baseball pitching performance. Static stretching of the shoulder may be performed during a warm-up before a throwing activity.